2017
DOI: 10.1037/fam0000245
|View full text |Cite
|
Sign up to set email alerts
|

Marital, parental, and whole-family predictors of toddlers’ emotion regulation: The role of parental emotional withdrawal.

Abstract: The present study aims to address how dyadic and triadic family interactions across the transition to parenthood contribute to the later development of toddlers' adaptive emotion regulation using structural equation modeling methods. Specifically, we examined the interrelations of observed marital negative affect before childbirth, parents' emotional withdrawal during parent-infant interactions at 8 months, and coparenting conflict at 24 months as predictors of toddlers' adaptive emotion regulation at 24 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
1
39
3
2
Order By: Relevance
“…Finally, we did not find support for our “spillover” hypothesis that parents who were less supportive of their spouse would be more involved in parental decision making. It may be that fathers who are less supportive of mothers may be experiencing more distress in the marital relationship because negativity in the marital relationship is often related to greater withdrawal from parenting involvement, as we found in another study using the same data set as the current study (Gallegos et al, ). However, it is somewhat surprising that this path was not significant for mothers.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Finally, we did not find support for our “spillover” hypothesis that parents who were less supportive of their spouse would be more involved in parental decision making. It may be that fathers who are less supportive of mothers may be experiencing more distress in the marital relationship because negativity in the marital relationship is often related to greater withdrawal from parenting involvement, as we found in another study using the same data set as the current study (Gallegos et al, ). However, it is somewhat surprising that this path was not significant for mothers.…”
Section: Discussionsupporting
confidence: 65%
“…Other research has suggested that fathers' sensitive involvement with their young children may play a particularly important role in the development of their children's emotion regulation. Markedly, fathers' sensitive and stimulating play has been found to predict their toddlers' ability to adaptively regulate their emotions (using the same data set as current study; Hazen, McFarland, Jacobvitz, & Boyd‐Soisson, ), whereas fathers' emotional withdrawal from their toddlers is predictive of toddlers' greater emotional dysregulation (using the same data set as the present study; e.g., Gallegos, Murphy, Benner, Jacobvitz, & Hazen, ). Given that cooperative coparenting is characterized by high mutual support and involvement, fathers' higher involvement should be associated with cooperative coparenting, because fathers are likely to be more involved in parental decision making when their wives are supportive of their parenting decisions, whereas maternal involvement is likely to be high regardless of paternal support.…”
Section: Theoretical Backgroundmentioning
confidence: 55%
See 1 more Smart Citation
“…Because the family climate is shown to be important for the development of emotion regulation in children (Morris et al., ), children in less‐functional families may not have developed optimal emotion regulation skills; thus, they might undereat because they lack strategies for dealing with negative emotions. In support of this view, one recent study found that conflict between parents was significantly associated with less adaptive emotion regulation in toddlers (Gallegos et al., ). Finally, it should be noted that we only detected a small effect of family functioning, and the practical relevance of this finding is thus uncertain.…”
Section: Discussionmentioning
confidence: 89%
“…It may be that findings can be attributed to the differing coding systems, or to the presence of the mother in the triadic task, as opposed to differing parenting contexts (play vs. stress). For example, extant research has found that dyadic and triadic caregiving contexts have intercorrelated, yet unique impacts on childhood socioemotional development (Johnson, ; Johnson, Cowan, & Cowan, ; Murphy et al, ), and specifically on the development of emotion regulation in toddlerhood (Gallegos et al, ). Although the current study did not assess whole family functioning, per se, the significance of fathering in a broader (triadic) family context suggests that this is an important avenue for continued investigation.…”
Section: Discussionmentioning
confidence: 99%